Analysis of State Civil Response to Thematic Bureaucratic Reform Implementation and Perception - Sabtian, Yoki Tulus; Natasha, Catherine Eugene; Djati, Dhefara Hersaning (Journal of Transformative Governance and Social Justice, 2024)
Thematic bureaucratic reforms allow the government to focus more on addressing challenges in specific sectors so that the results can be felt directly by the public. This study aims to explore deeper responses, views, and perceptions of a small number of State Civil Apparatus (ASN) to the Thematic Bureaucratic Reform Reaction. The method used in this study is a qualitative study with an exploratory approach using an open questionnaire that allows respondents to provide narrative responses regarding their views, reactions, and perceptions of the reform program. The study was conducted in the Organization Section of Lampung Province as one of the OPD (Regional Apparatus Organization) that has implemented thematic bureaucratic reforms. The result obtained in this research is the lack of understanding of the State Civil Apparatus (ASN) regarding preparing the Thematic Bureaucratic Reform roadmap. However, civil servants have tried to compile the roadmap as a reference for preparing government programs. The involvement of civil servants in the preparation of the thematic bureaucratic reform roadmap has also been. What can be developed next is the existence of research or socialization related to how to technically prepare a thematic bureaucratic reform roadmap according to procedures so that it can be implemented properly.